2019
DOI: 10.1515/bmc-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Primary Hydatid Cyst of Thyroid Gland: A Case Report

Abstract: A 34-year-old female patient was presented to the general surgery clinic of the hospital complaining of a growing tangible swelling in her neck. In physical examination, the patient had two palpable soft nodules in the left lobe of the thyroid which hadn’t invaded the surrounding tissues. The function of thyroid gland was normal and fine needle aspiration (FNA) result reported it benign. The patient went through a left lobectomy and isthmectomy. The histopathology report concluded a nodular hyperplasia and a H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Hydatid cysts can affect many organs in the body [ 46 ], including the thyroid gland, gallbladder, pancreas, uterus and adnexa, seminal vesicles, bones, muscles, skin, and subcutaneous tissue [ 47 ]. Hydatid cysts have been reported in the orbit as a retrobulbar cystic lesion that is confirmed by histopathology examination [ 48 ] in the left lobe of the thyroid gland mimicking colloid cysts and leading to left lobectomy and isthmectomy [ 49 ], and in the submandibular salivary gland mimicking enlarged lymph nodes diagnosed by fine-needle aspiration cytology [ 50 ]. They have been reported in parotid salivary glands leading to cystectomy with partial parotidectomy [ 51 ]; in the female breast, mimicking a breast mass forming diagnostic dilemma [ 52 ]; and in the male breast, mimicking a breast mass leading to lumpectomy where the diagnosis was confirmed on a histopathology examination [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid cysts can affect many organs in the body [ 46 ], including the thyroid gland, gallbladder, pancreas, uterus and adnexa, seminal vesicles, bones, muscles, skin, and subcutaneous tissue [ 47 ]. Hydatid cysts have been reported in the orbit as a retrobulbar cystic lesion that is confirmed by histopathology examination [ 48 ] in the left lobe of the thyroid gland mimicking colloid cysts and leading to left lobectomy and isthmectomy [ 49 ], and in the submandibular salivary gland mimicking enlarged lymph nodes diagnosed by fine-needle aspiration cytology [ 50 ]. They have been reported in parotid salivary glands leading to cystectomy with partial parotidectomy [ 51 ]; in the female breast, mimicking a breast mass forming diagnostic dilemma [ 52 ]; and in the male breast, mimicking a breast mass leading to lumpectomy where the diagnosis was confirmed on a histopathology examination [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sachar et al reported that hydatid cyst can affect thyroid gland, breast, gallbladder, pancreas, uterus and adnexa, seminal vesicles, bones, muscles, skin and subcutaneous tissue [6] . In the literature, hydatid cyst was reported in the orbit [7] , the breast of a male patient [8] , the right ventricle of the heart [9] , the thyroid gland [10] , the subcutaneous region of face [11] , over the plantar surface of the foot [12] , and even in the posterior triangle of the neck of a 3-year-old child [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Not limited to liver and lung, our study revealed few other uncommon sites including abdominal external oblique muscle, soft tissue of thigh, peritoneal nodule, kidney and brain. Literatures review showed many other uncommon and rare locations like subcutaneous tissue [20], muscles [21][22][23], soft tissue [24], bone [25], pericardium [26], pleura [23], thyroid [27], gallbladder [4], spleen [4], uterus [28], ovary [3], breast [11], buccal mucosa [29], orbit [30], brain [11,31], and spine [32]. The liver is the first effective filter for most of the larvae after it penetrated the intestinal mucosa; therefore liver is the most common site of HD.…”
Section: Discussionmentioning
confidence: 99%